Synthesis of triazole-linked morpholino oligonucleotides via Cu1 catalysed cycloaddition - Palframan, Matthew J.; Alharthy, Rima D.; Powalowska, Paulina K.; Hayes, Christopher J. (Royal Society of Chemistry, 2016)
Triazole-linked morpholino (TLMO) oligonucleic acids were synthesised using the CuI catalysed (3 + 2) azide–alkyne cycloaddition (CuAAC) reaction. The modified DNA analogues were incorporated into 13-mer sequences via solid phase synthesis. UV melting experiments showed that the TLMO modification gives higher Tm values than the corresponding TLDNA modification.